Transformation of the Genre of Folk Puppet Comedy in D. Rubina’s Novel Petrushka’s Syndrome - Szabó, Tünde (Literatūra, 2025)
The image of the protagonist in Dina Rubina’s novel Petrushka’s Syndrome is closely connected with the folk puppet theatre character, Petrushka. In addition to this connection, the plot of the novel also displays some features of the folk comedy Petrushka’s Theatre. The article examines how, partly through the psychosexual symbolism of the narrative, Rubina reinterprets and re-accentuates specific compositional features of folk comedy that constitute its ‘genre’s backbone’ (M. Bakhtin). The limited set of characters and scenes in Petrushka’s theater are transformed in Petrushka’s Syndrome into the fates of ‘real people’ with complex family relationships. These relationships lend themselves to psychoanalytic interpretation. Three of the characters, inclined toward uncontrolled promiscuity, are punished with symbolic castration or the inability to continue their lineage through the paternal line. One character, who consciously rejects promiscuity and possesses a creative, life-affirming impulse, changes his destiny and overcomes death, thereby transforming the ending of the Petrushka theater’s plot.
Keywords: Dina Rubina; Petrushka’s Syndrome; Petrushka’s Theater; Z. Freud; castration complex